The Impact of Crowd Psychology on Stock Market Cycle Case of Vietnam Stock Market - Yen Xuan, Phan Ngoc; Giang, Le Truong (International Journal Of Management And Economics Invention, 2022)
The stock market plays an increasingly important role in the economy, it is a place to raise capital for businesses, increase liquidity and provide many profit-seeking opportunities for individual investors. However, investing in the stock market is not easy, most investors are influenced by the crowd psychology, they have similar actions when influenced by the crowd, this creates cycles of the stock market. The article studies the influence of crowd psychology on Vietnamese investors by surveying 120 individual investors and analyzing investor psychology in phases of the Vietnamese stock market cycle. The results show that the majority of Vietnamese investors decide to choose stocks chosen by many other investors and they easily react when the crowd reacts. The Vietnamese stock market also goes through the same psychological cycles as the stock markets in other countries. Currently, the Vietnamese stock market is expected to be in a period of thrill or euphoria. Investors should be cautious and carefully consider their investment decisions so as not to fall into a state of panic and sell-off.